-5x-6(6-5x)=6(3x+1)

Simple and best practice solution for -5x-6(6-5x)=6(3x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-6(6-5x)=6(3x+1) equation:



-5x-6(6-5x)=6(3x+1)
We move all terms to the left:
-5x-6(6-5x)-(6(3x+1))=0
We add all the numbers together, and all the variables
-5x-6(-5x+6)-(6(3x+1))=0
We multiply parentheses
-5x+30x-(6(3x+1))-36=0
We calculate terms in parentheses: -(6(3x+1)), so:
6(3x+1)
We multiply parentheses
18x+6
Back to the equation:
-(18x+6)
We add all the numbers together, and all the variables
25x-(18x+6)-36=0
We get rid of parentheses
25x-18x-6-36=0
We add all the numbers together, and all the variables
7x-42=0
We move all terms containing x to the left, all other terms to the right
7x=42
x=42/7
x=6

See similar equations:

| 19=s−21 | | 10q=-2(-5q-18)+16 | | m+49=57 | | 3x+9-5x=23 | | -14x^2+7x-16=0 | | -8+16n=-2(-8n+4) | | Y2x-6=x-14 | | 5x+20=4x+10=x6 | | (t)=−20+11t | | 2(x-3)+2=-3(x+8) | | -4(2x+3)=2x+6-(8x=2) | | m5=7 | | 15x-24-4x=-76 | | 57+62+43+b=55 | | -5f+12-11f=12-16f | | 4y+3-2y=9+y-3 | | 2(7+3m)=8(1+m) | | 6x-4=x-16 | | -19+2r=6r-5-4r | | -6x+5-x=82 | | -4b-(4b+8)=2(b+6) | | M=-10x-x | | -3d+5+8=2d-17 | | 7x+72=2x-36 | | 3b^2-b+4=4 | | x+4/7=(3/8) | | -3(8k+6)=-3(4k+6) | | 2(6x+4)-6=2x=3(4x+3)+1 | | 5x+20=4x+10 | | 15+15t=3t-13+12t | | (8x^2)+22x+9=0 | | 7k-5=-15 |

Equations solver categories